AB0786 Knee Osteoarthritis and Functional Changes in Ankle Joint and Achilles Tendon. (10th June 2014) - Kalichman, L.; Magram, I.; Reitblat, T.
Abstract : Background: Very few studies studied the relationship between knee OA and ankle joint parameters. Function of ankle joint and gastrocnemius muscle play important role in normal knee functioning, and should be studies in context of knee OA. Objectives: To evaluate the association between tibiofemoral knee osteoarthritis (OA) and degenerative changes in the Achilles tendon and functional parameters of the ankle joint: active range of motion (AROM) of dorsiflexion and strength of gastrocnemius. To evaluate factors associated with degenerative changes in Achilles tendon. Methods: A case-control observational study was conducted in APOS Therapy Center, Medical and Sports Technologies Ltd., Israel. For this study, 93 participants ≥50 years old, with no previous ankle injuries were recruited: 63 patients with bilateral or unilateral knee OA (Kellgren- Lawrence [K-L] score ≥2) and a control group (N=30) of age, sex and Body Mass Index (BMI) matched volunteers without knee OA. Participants filled out the Western Ontario and McMaster Osteoarthritis Index (WOMAC) questionnaire. A clinical examination included measurement of weight, height, AROM of ankle dorsiflexion, Achilles tendon thickness and gastrocnemius muscle strength. Results: Subjects in the knee OA group were not significantly different from the healthy controls regarding the age, height and left Achilles tendon width (p=0.053, p=0.198, p=0.184, correspondingly). Achilles tendon width in the symptomatic leg in the knee OA group was significantly thicker (17.07±3.44 mm.) compared to the non-symptomatic one (15.96±3.72 mm.) (p=0.010). Ankle dorsiflexion AROM in individuals with knee OA was significantly lower (7.27±5.50°) in the symptomatic leg than in the non-symptomatic one (8.65±5.68°) (p=0.012). No such differences were found between dominant and other leg in control group. K-L of medial compartment was positively correlated with Achilles tendon thickness of the symptomatic leg in the knee OA group (r=0.255 p=0.044). Active heel raises from the floor in individuals with knee OA showed significant negative correlation with Achilles tendon thickness of the symptomatic leg (r=-0.491 p<0.001, rs =-0.475 p<0.001, correspondingly). Conclusions: This is a first study that evaluated the physical parameters of the ankle joint and Achilles tendon degeneration in knee OA patients. Individuals with symptomatic tibiofemoral knee OA compared to the healthy controls have a high prevalence of ipsilateral degenerative changes in Achilles tendon, decreased active ankle joint dorsiflexion and decreased strength of gastrocnemius muscle. Comprehensive assessment of Achilles tendon and of the ankle joint should be part of knee OA evaluation process. References: Guler, H., Karazincir, S., Turhanoglu, A. D., Sahin, G., Balci, A., & Ozer, C. (2009). Effect of coexisting foot deformity on disability in women with knee osteoarthritis. Journal of the American Podiatric Medical Association, 99(1), 23-27. Hicks-Little, C. A., Peindl, R. D., Hubbard, T. J., Scannell, B. P., Springer, B. D., Odum, S. M., Fehring, T. K., & Cordova, M. L. (2011). Lower extremity joint kinematics during stair climbing in knee osteoarthritis. Medicine and Science in Sports and Exercise, 43(3), 516-524. Reilly, K., Barker, K., Shamley, D., Newman, M., Oskrochi, G. R., & Sandall, S. (2009). The role of foot and ankle assessment of patients with lower limb osteoarthritis. Physiotherapy, 95(3), 164-169. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1620